Penerapan Pembelajaran dengan Menggunakan Metode Resitasi Untuk Meningkatkan Aktivitas, Kemampuan Bekerjasama dan Hasil Belajar Matematika di SDN Dawuhan Sengon II Purwodadi Pada Pokok Bahasan Pengerjaan Hitung Bilangan Pecahan - Murdiani, Endang (LPPM Universitas Bina Bangsa, 2022)
Class action research (PTK) has been carried out at SDN Dawuhan Sengon II Purwodadi, Purwodadi District, in class VI students in Mathematics subjects with the subject matter of Working on Calculating Fractional Numbers. The learning method used is a resitation method where the teacher gives certain tasks so that students carry out learning activities both individually and in groups. This method was chosen because there is too much study material while there is little available time. This class action research is carried out in 3 cycles, and each cycle consists of three meetings. The results of this action study showed very significant progress both in terms of student activities, participation, the ability to cooperate well and learning outcomes in the form of written test scores. The average score of mathematics learning outcomes before the holding of PTK (On Broad and Volume Subjects) was 61.37; then increased after being given action by the resitation method on cycles I, II, and III respectively was 62.81; 65,63; 71.56. Thus it can be concluded that classroom action research using the resitation method can help solve the problems of teachers in the classroom and can improve student learning outcomes in mathematics subjects